Association between TSH Values and GFR Levels in Euthyroid Cases with Metabolic Syndrome - H. Keskin; K. Cadirci; K. Gungor; T. Karaaslan; T. Usta; A. Ozkeskin; A. Musayeva; F. Yesildal; F. Isman; H. Y. Zengin (International Journal of Endocrinology)
Background. Metabolic syndrome (MetS) is associated with the risk of developing chronic kidney disease. Although the negative effects of high thyroid-stimulating hormone (TSH) values on glomerular filtration rate (GFR) levels have been known for years, the negative effects of increased TSH on GFR in euthyroid cases have been reported in recent years. This study was aimed at investigating the association between the effect of increased TSH values and estimated-GFR (eGFR) levels in euthyroid cases with MetS. Methods. For this hospital-based descriptive study, 191 MetS cases (123 females, 68 males) were evaluated. Those whose TSH was not within 0.5–4.5 uIU/mL, eGFR was <40 mL/min/1.73 m2, and/or reported any thyroid/kidney disease were excluded. Partial correlation coefficients were calculated to investigate the relationship between the eGFR values and several other numerical variables while controlling for age and BMI in addition to the adjusted gender effect. Thereafter, the multiple linear regression analysis with a stepwise variable selection approach was used to reveal the independent factors that could affect the logarithmically transformed eGFR. Results. The median age was 52 (19–65) years, the median eGFR was 94.3 (41.3–194) mL/min/1.73 m2, and the median TSH was 1.58 (0.50–4.50) uIU/mL in the whole group. Increased TSH even in the normal range was associated with eGFR after adjusting for age and body mass index (BMI), especially in females. The high age (b = −0.160, p=0.005), high BMI (b = −0.134, p=0.020), high TSH (b = −0.380, p<0.01), and high uric acid (b = −0.348, p<0.01) were found as significant predictors of the eGFR in MetS patients. Conclusion. Independent of age and BMI, elevated TSH even in the euthyroid range showed an association with the eGFR in female MetS cases who had normal kidney functions. This correlation was stronger than the correlations between the eGFR and the MetS diagnostic parameters. These findings need further studies on the issue..